SEJARAH DAKWAH DI MAKASSAR - Syamsuri Syamsuri (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2014)
This paper deals with the Islamic da’wah in Makassar. Islam in this area coincided with the culture and structure of society. Those who hold an authority are forced to go hand in hand with society to concern with Islam in order to be regarded as‚pious and religious‛. A variety of symbols are displayed as a scenario to please people. Such symbols are a dome of mosque, religiosity, pilgrimage (hajj), ‘umrah, and designation of‚ guru mengaji‛ (religious teacher). Cultural Islam has a great impact on those in authority as an agent. Along with the history of da’wah in Makassar, history always forces those in authority to go in and out as a moment of creating image, and da’wah was made as commodity.